A DISCOURSE ANALYSIS OF COLLOCATION IN ENGLISH TEXTBOOK FOR GRADE X IN THE SENIOR HIGH SCHOOL - Chairunnisa Lubis; Zainuddin (Universitas Negeri Medan, 2016)
This study aims to analyze the use of collocation in English Textbook forGrade X in The Senior High School. The objective of this study was to identify thetypes of collocation which used in the textbook and how it was used in the Englishtextbook. The source of the data was English Textbook for Grade X in The SeniorHigh School from Book of Matters Centre of Ministry of Education. The data werecollected after read whole textbook. The data took from ll genre in reading text. In thetextbook, there were 5 genre of reading text. They were Narrative, Recount,Descriptive, Procedure and News Item. The results of this study were 6 types ofcollocation which used in the etxtbook. They were Adjective and Nouns, Verbs andNouns, Noun + noun, Verbs and expression of preposition, Verbs and adverbs,Adverbs and adjectives. The most dominant type of collocation was Verb and Nounscollocation.